2004
DOI: 10.1038/oby.2004.54
|View full text |Cite
|
Sign up to set email alerts
|

Hip Circumference and Cardiovascular Morbidity and Mortality in Men and Women

Abstract: HEITMANN, BERIT L., PEDER FREDERIKSEN, AND LAUREN LISSNER. Hip circumference and cardiovascular morbidity and mortality in men and women. Obes Res. 2004;12:482-487. Objective: It has recently been demonstrated that, in middleaged women, a wide hip circumference is a protective factor for a number of health endpoints in later years. The effect seems to be independent of both overweight and waist circumference. This paper aims to replicate this finding in another population-based sample consisting of women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 9 publications
6
107
0
3
Order By: Relevance
“…Therefore, loss of abdominal fat may reduce the risk of cardiovascular morbidity and mortality, whereas fat on the lower body or in the peripheral sub cutis may have favourable effects on cardiovascular risk factors, and loss of such tissues may increase the risk of cardiovascular morbidity and mortality. [52][53][54][55][56] A few studies have reported a preferential loss of unhealthy visceral fat after physical activity, but the results from previous literature are inconsistent. [23][24][25][26][27] Data on change in fat distribution were not available and thus this could not be examined in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Therefore, loss of abdominal fat may reduce the risk of cardiovascular morbidity and mortality, whereas fat on the lower body or in the peripheral sub cutis may have favourable effects on cardiovascular risk factors, and loss of such tissues may increase the risk of cardiovascular morbidity and mortality. [52][53][54][55][56] A few studies have reported a preferential loss of unhealthy visceral fat after physical activity, but the results from previous literature are inconsistent. [23][24][25][26][27] Data on change in fat distribution were not available and thus this could not be examined in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Compared with the well-established association of central fat with disease risks, there are only a few studies regarding the association of the lower-body fat depot, which is very predominant in women, with metabolic diseases. Among the limited relevant studies, most of them reported inverse associations between hip circumference and mortality or heart diseases (3,27,(44)(45)(46)(47)(48)(49)(50)(51) . Nevertheless, hip circumference was not associated with CHD or other metabolic diseases without adjusting for waist circumference or BMI and the effect of central obesity on mortality risk could be seriously underestimated without adjusting for hip circumference (3,52) .…”
Section: Discussionmentioning
confidence: 99%
“…6 On the other hand, a narrow hip circumference seems to have an independent and inverse association with the risk of type 2 diabetes 7 and CVD morbidity and mortality. [8][9][10] Carotid intima-media thickness (IMT), measured noninvasively by ultrasonography, predicts future risk of myocardial infarction and stroke, and a change in carotid IMT has been validated as a vascular marker of the progression of preclinical atherosclerosis. 11 Carotid ultrasonography is a more suitable technique for assessing the progression of preclinical atherosclerosis than the quantification of coronary calcium, especially in the elderly, most of whom have coronary calcification.…”
Section: Introductionmentioning
confidence: 99%